A successfully treated case of Lemmel syndrome with pancreaticobiliary maljunction: A case report. (2020) - Yanagaki, Mitsuru; Shiba, Hiroaki; Hagiwara, Shin; Hoshino, Masato; Sakuda, Hitoshi; Furukawa, Yoshiyuki; Yanaga, Katsuhiko
Highlights: Lemmel syndrome is a rare condition that leads to cholangitis and/or pancreatitis due to intraduodenal diverticulum. Surgery is considered for the treatment of severe or repeated symptoms in patients with this condition. We herein report a successfully diagnosed and treated case of Lemmel syndrome with pancreaticobiliary maljunction. Abstract: Background: Lemmel syndrome is a rare condition that leads to cholangitis and/or pancreatitis due to intraduodenal diverticulum. Surgery is considered for the treatment of severe or repeated symptoms in patients with this condition. Case presentation: An 81-year-old woman was admitted to our hospital, complaining of general fatigue, BT 38.8 degree, and right hypochondoralgia. Her hepatobiliary enzyme levels were elevated, and enhanced abdominal computed tomography revealed dilation of the common bile duct and intraduodenal diverticulum. After restarting oral intake, her symptoms were exacerbated. Endoscopic retrograde cholangio-pancreatography (ERCP) revealed pancreaticobiliary maljunction and parapapillary diverticulum. Under a diagnosis of Lemmel syndrome with pancreaticobiliary maljunction complicated by acute pancreatitis and cholangitis, we performed extrahepatic bile duct resection with cholecystectomy and papilloplasty. Her postoperative course was uneventful, and the patient was discharged 20 days after surgery. She remains well at 5 months after surgery. Conclusion: We herein report a successfully diagnosed and treated case of Lemmel syndrome with pancreaticobiliary maljunction.